A Rare Case of Unilateral Tongue Edema with Angiotensin Converting Enzyme Inhibitors - Beatriz Gil Braga; Márcia Cravo; Pedro Neves; Filipe Pinto; Catarina Mendonça (Acta Médica Portuguesa, 2022)
Angiotensin converting enzyme inhibitors (ACEi) are widely used for the treatment of multiple conditions such as hypertension, heart failure and chronic kidney disease. Angioedema is a rare but potentially fatal complication of ACEi use and unilateral tongue edema is a very rare presentation. We report a case of a 55-year-old man, with a history of hypertension, on enalapril for three years, who presented to the hospital with unilateral tongue swelling, without airway compromise. Other causes were excluded and the diagnosis of angioedema due to enalapril was established. The patient was discharged with discontinuation of ACEi with total resolution of symptoms and without relapse after several months. Although very rare, unilateral tongue swelling should be considered in the presentation of angioedema associated with ACEi. Tight surveillance is important to prevent fatal complications such as airway obstruction. ACEi discontinuation is crucial to avoid clinical relapse.